Experimental analysis on mechanical properties of different varieties hop stems. Issue 1 (1st November 2022) - Yang, Jing; Ma, Zhaoyi; Zhang, Shaoqiang; Li, Xiaokang; Luo, Haiyu; Feng, Yanwei
Abstract : So as to explore the mechanical properties of different varieties hop stems during the harvest period and resolve the problems of weak applicability in the cutting device of the hops harvester, this paper took the hops stems such two varieties as Qingdao Flower and Marco Polo as samples, and carried out tensile and cutting tests by using the universal testing machine. The tensile stress, tensile strength, elastic modulus and other mechanical indexes of the stems were measured by tensile test. The test results show that the stems of Marco Polo are thicker than those of Qingdao Flower. The tensile stress of Marco Polo is higher than that of Qingdao Flower and the tensile strength of Marco Polo is smaller than that of Qingdao Flower. The elastic modulus of Marco Polo is almost half of Qingdao Flower. The single factor test was carried out with the factors of cutting speed, cutting mode and water content. The single factor test shows that when cutting speed increase from 50mm / min to 250mm / min, the cutting strength of two stems first decrease and then tend to be stable. When the cutting modes are oblique cutting, transverse cutting and sliding cutting, the cutting strength decreases in turn. In the same cutting mode, the cutting strength of Qingdao Flower is greater than that of Marco Polo. With the increase of water content, the cutting strength of the two stems decreases significantly. On this basis, the orthogonal test was performed to determine the best cutting parameters. The orthogonal test shows that the primary and secondary order of the influence in test factors on cutting strength is water content, cutting mode and cutting speed. The effect of water content on Marco Polo cutting strength is extremely significant, and it has a significant effect on Qingdao Flower; The effect of cutting mode on the cutting strength of two kinds of stems is significant, while the effect of cutting speed on the cutting strength of two kinds of stems is not significant. The best cutting parameters of hops stems are fresh sample, speed of 100 mm / min, sliding cutting mode. The above analysis supplies a theoretical foundation for designation and optimization the cutting device.